Penggunaan Media Gambar Interaktif Pada Materi Organ Pencernaan Manusia Untuk Meningkatkan Hasil Belajar Peserta Didik Di Kelas V Di SD Negeri 2 Kancilan - Enik Krisnawati (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
This Learning Improvement Research aims to determine whether or not there is an influence of interactive image media in increasing the activity and learning outcomes of grade V science students at SD Negeri 2 Kancilan. The subjects of this research were class V students at SD Negeri 2 Kancilan Kembang Jepara, totaling 24 students. The learning activity data collection technique was carried out using the observation method. The results of this research state that student learning outcomes in science subjects regarding the Human Digestive Organs are still very poor. This is because there are still many students whose scores are below the KKM. Of the 24 students, only 5 students passed the Minimum Graduation Criteria (KKM), namely 70. For this reason, this research was carried out and it is hoped that using interactive image media can improve student learning outcomes on the subject of human digestive organs.